Elevated insulin‐like growth factor binding protein‐1 (IGFBP‐1) in men with metastatic prostate cancer starting androgen deprivation therapy (ADT) is associated with shorter time to castration resistance and overall survival. Issue 3 (16th October 2013) - Sharma, Jaya; Gray, Kathryn P.; Evan, Carolyn; Nakabayashi, Mari; Fichorova, Raina; Rider, Jennifer; Mucci, Lorelei; Kantoff, Philip W.; Sweeney, Christopher J.
Abstract BACKGROUND Insulin‐like growth factor (IGF) and adipokines have been implicated in prostate cancer carcinogenesis. METHOD Data from 122 men with serum samples drawn within 3 months of starting ADT for metastatic prostate cancer was accessed retrospectively. IGF‐1, IGF binding protein (BP)‐1, leptin, and adiponectin levels were measured by multiplex electrochemiluminescence assays. A multivariable Cox model assessed the association of time to castration resistant prostate cancer (CRPC) and overall survival by the protein levels, adjusted for clinical variables, age and prostate specific antigen (PSA) levels at start of ADT, race, ECOG status, extent of metastases and were reported as hazard ratio (HR) with 95% confidence interval (CI). RESULTS Median follow‐up and overall survival were 44 and 42.2 months, respectively. ECOG performance status (≥1 vs. 0) was negatively associated with overall survival [HR = 2.8 (1.1–7.0), P = 0.03], and PSA nadir <0.2 was predictive of longer time to CRPC [HR = 0.3 (0.2–0.5), P < 0.0001]. The median time to CRPC by low, middle, and top IGFBP‐1 tertile distribution was 20.7, 18.1, and 12.4 months, respectively, with HR for middle versus low tertile levels 3.1 (1.7–5), P = 0.0003, and for top versus low tertile levels was 2.4 (1.3–4.2), P = 0.003. The median overall survival by low, middle and top tertile IGFBP‐1 level was 48.5, 46.4, and 32.8 months, respectively, with HR for top versus low tertile 2.5 (1.2–5.1), P = 0.01. There was no association with IGF‐1, adiponectin and leptin. CONCLUSION Elevated IGFBP‐1 appears to be associated with shorter time to CRPC and lower overall survival in men with metastatic prostate cancer. Prostate 74:225–234, 2014. © 2013 Wiley Periodicals, Inc.